2017
DOI: 10.1016/j.rbmo.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after IVF or ICSI using human blastocysts derived from oocytes containing aggregates of smooth endoplasmic reticulum

Abstract: In this study the clinical and neo-natal outcomes after transfer of blastocysts derived from oocytes containing aggregates of smooth endoplasmic reticulum (SER) were compared between IVF and intracytoplasmic sperm injection (ICSI) cycles. Clinical and neo-natal outcomes of blastocysts in cycles with at least one SER metaphase II oocyte (SER + MII; SER + cycles) did not significantly differ between the two insemination methods. When SER + MII were cultured to day 5/6, fertilization, embryo cleavage and blastocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 25 publications
8
24
0
Order By: Relevance
“…We previously reported that sERC formation was related to higher serum estradiol levels detected in sERC positive cycles and this is in agreement with other studies [2,9]. Very recently, Canto et al reported that sERC positive oocytes had greater spindle lengths and widths compared with control oocytes.…”
Section: Introductionsupporting
confidence: 91%
“…We previously reported that sERC formation was related to higher serum estradiol levels detected in sERC positive cycles and this is in agreement with other studies [2,9]. Very recently, Canto et al reported that sERC positive oocytes had greater spindle lengths and widths compared with control oocytes.…”
Section: Introductionsupporting
confidence: 91%
“…[789101214151617] Eight studies have reported clinical pregnancy as an outcome[7891014151617] and four have reported live birth rate. [1081617] Of the eight studies, all studies have a lower pregnancy rate in SERa oocytes, but only in one study, the difference reached statistical significance. [15] There was no difference in the live birth rate reported in the four studies between SERa oocytes and normal oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[3131415] Very few prior studies have reported live birth rate as a primary outcome measure. [8101617] Moreover, following the 2011 recommendations, there were three publications in 2013 which reported the birth of normal babies originating from oocytes containing SERa. [81718] Discarding oocytes containing SERa increases the risk of cycle cancellation with no embryos available for transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of pregnancy and neonatal outcomes, transfer of SERa-positive embryos was associated with 20% increased risk of miscarriage (Braga et al 2013), while women with SERa oocytes tended to deliver earlier, were characterized by a higher percentage of obstetric complications during pregnancy and a significantly lower birthweight in singletons compared to unaffected women (Ebner et al 2008). The rate of neonatal death was alarmingly high in the SERa group compared to healthy counterparts (Ebner et al 2008), although subsequent studies were more reassuring, reporting similar fertilization and pregnancy rates, as well as similar malformation rates between SERa-positive and SERa-negative cycles (Ebner et al 2013;Mateizel et al 2013;Hattori et al 2014;Itoi et al 2017). The adverse obstetric outcome observed in the present case report may be attributed to a procedure-related effect of amniocentesis (Akolekar et al 2015;Alfirevic et al 2017), although the presence of SERa in oocytes cannot be excluded as a potential cause.…”
Section: Discussionmentioning
confidence: 97%